2009
DOI: 10.1063/1.3245338
|View full text |Cite
|
Sign up to set email alerts
|

Electrical triggering of metal-insulator transition in nanoscale vanadium oxide junctions

Abstract: 200 nm diameter Au contacts were fabricated by e-beam lithography on sputtered thin film vanadium oxide grown on conducting substrates and current perpendicular to plane electron transport measurements were performed with a conducting tip atomic force microscope. Sharp jumps in electric current were observed in the I-V characteristics of the nano-VO2 junctions and were attributed to the manifestation of the metal-insulator transition. The critical field and dielectric constant were estimated from quantitative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
77
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 99 publications
(81 citation statements)
references
References 34 publications
4
77
0
Order By: Relevance
“…8 for all compositions of doped VO 2 . Room temperature carrier density was found to be 3 x10 19 cm −3 which is similar to that reported by Ruzmetov et al 29 It was observed that with an increase in tungsten content, carrier concentration increased from 3x10 19 cm −3 for the undoped sample to 1.7x10 22 concentration. Tungsten with W 6+ valence when substituting for the V 4+ gives electrons per atom thereby increasing the number of charge carriers.…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…8 for all compositions of doped VO 2 . Room temperature carrier density was found to be 3 x10 19 cm −3 which is similar to that reported by Ruzmetov et al 29 It was observed that with an increase in tungsten content, carrier concentration increased from 3x10 19 cm −3 for the undoped sample to 1.7x10 22 concentration. Tungsten with W 6+ valence when substituting for the V 4+ gives electrons per atom thereby increasing the number of charge carriers.…”
Section: Resultssupporting
confidence: 78%
“…9 MIT in VO 2 can also be triggered by optical, 17 electrical, 18 mechanical means. [17][18][19] Characteristics of the transition is influenced by the nature of the phases (M1, M2, T, R), microstructure (i.e. morphology and relative orientation of the grains and the grain boundaries) 20 and doping.…”
Section: Introductionmentioning
confidence: 99%
“…The VO 2 film on Nb-doped SrTiO 3 shows over two orders of magnitude resistance change across the transition. The VO 2 film on RuO 2 buffered TiO 2 shows a two step transition.…”
Section: Discussionmentioning
confidence: 99%
“…To date, VO 2 films have primarily been grown on conducting substrates such as heavily-doped Si or Ge, and Pt [3][4][5]. As far as conducting oxide substrates are concerned; there is a recent report discussing the role of twin boundaries of VO 2 grown on Ga-doped ZnO buffered c-sapphire [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation